Optimized Loading Dose Strategies for Bedaquiline When Restarting Interrupted Drug-Resistant Tuberculosis Treatment - Koele, Simon E; van Beek, Stijn W; Maartens, Gary; Brust, James C M; Svensson, Elin M (Antimicrobial agents and chemotherapy, 2022)
Interruption of treatment is common in drug-resistant tuberculosis patients. Bedaquiline has a long terminal half-life; therefore, restarting after an interruption without a loading dose could increase the risk of suboptimal treatment outcome and resistance development. We aimed to identify the most suitable loading dose strategies for bedaquiline restart after an interruption. A model-based simulation study was performed. Pharmacokinetic profiles of bedaquiline and its metabolite M2 (associated with QT prolongation) were simulated for 5,000 virtual patients for different durations and starting points of treatment interruption. Weekly bedaquiline area under the concentration-time curve (AUC) and M2 maximum concentration ( ) deviation before interruption and after reloading were assessed to evaluate the efficacy and safety, respectively, of the reloading strategies. Bedaquiline weekly AUC and M2 deviation were mainly driven by the duration of interruption and only marginally by the starting point of interruption. For interruptions with a duration shorter than 2 weeks, no new loading dose is needed. For interruptions with durations between 2 weeks and 1 month, 1 month and 1 year, and longer than 1 year, reloading periods of 3 days, 1 week, and 2 weeks, respectively, are recommended. This reloading strategy results in an average bedaquiline AUC deviation of 1.88% to 5.98% compared with -16.4% to -59.8% without reloading for interruptions of 2 weeks and 1 year, respectively, without increasing M2 . This study presents easy-to-implement reloading strategies for restarting a patient on bedaquiline treatment after an interruption.